2022
DOI: 10.3390/plants11233211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foliar Application of ZnO and Fe3O4 Nanoparticles on Seed Yield and Physio-Biochemical Parameters of Cucumber (Cucumis sativus L.) Seed under Open Field and Protected Environment vis a vis during Seed Germination

Abstract: Nutritionally rich cucumber seeds remain in demand in the agricultural, health and cosmetic sectors as they are essential for a successful crop stand establishment and seed-based products. However, the production of cucumber seeds is impeded by source limitation and nutrient deficiency. The foliar application of micronutrients can supplement this deficiency and overcome the physiological setback. An experiment was undertaken to compare the impacts of the foliar application of Fe and Zn, as nanoparticles and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…This indicates that CsTAU1 has a certain impact on CAT content and improving cucumber's resistance to salt-alkali stress by reducing H 2 O 2 to H 2 O. This result is similar to the research results of Nakul and Pal [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…This indicates that CsTAU1 has a certain impact on CAT content and improving cucumber's resistance to salt-alkali stress by reducing H 2 O 2 to H 2 O. This result is similar to the research results of Nakul and Pal [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…Gupta et al stated that increased antioxidant enzyme activity leads to homeostatic control of ROS levels in cells which in turn determines the state of the seeds during germination, dormancy, and senescence. They observed that foliar application of ZnO NPs and Fe 3 O 4 NPs in the range of 100-300 mg/L in an open field tends to improve physiobiochemical parameters and antioxidant enzyme activity (SOD, CAT, and POD) of Cucumis sativus L; however, above the optimum concentration of 300 mg/L, it showed a deleterious effect [64]. Treatment of Triticum aestivum plants with Fe 3 O 4 NPs (40-500 mg/L) showed prominent increase of Fe, P, and K content in its leaves with enhanced photosynthetic, respiration, and antioxidant enzyme activity (SOD, APX) thereby promoting the growth of plant [59].…”
Section: Estimation Of Lp El Proline Content and Sod Activitymentioning
confidence: 99%
“…Seed treatment is the application of fungicides, insecticides, inoculants, stimulants, biological products, or nutrients that preserve or improve seed performance, allowing crops to express their full genetic potential. It is a consolidated technique for cultivating crops, mainly soybean and corn, and avoiding possible losses resulting from the action of soil and shoot pests and the malformation of vegetative structures caused by a lack of nutrients in the early stages [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%